Correction: Witanto et al. Distributed Data Integrity Verification Scheme in Multi-Cloud Environment. Sensors 2023, 23, 1623 - Elizabeth Nathania Witanto; Brian Stanley; Sang-Gon Lee (Sensors, 2023)
The authors make the following corrections to the published paper [...]